Cell-Penetrating Peptides as a Tool to Deliver Biologically Active Recombinant Proteins to Generate Transgene-Free Induced Pluripotent Stem Cells - Chandrima Dey; Gloria Narayan; H Krishna Kumar; Manash P Borgohain; Nibedita Lenka; Rajkumar P Thummer (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2017)
Delivery of biologically active recombinant proteins using cell-penetrating peptides is a useful tool for transduction of molecular cargo into cells. This protein transduction technology is useful to understand the biological function of a specific protein of interest. Hence, it has been recently employed by severalgroups to understand the molecular functions of stem cell-specific transcription factors inpluripotent stem cells. Pluripotent stem cells have an indefinite self-renewal capacity and can be directed to differentiate into any desired cell type of an adult organism. The groundbreaking discovery of induced pluripotent stem (iPS) cells has revolutionized the field of stem cell research due to its immense potential in in vitro disease modeling, drug screening and regenerative medicine. Although, virus-based gene delivery approaches commonly used to generate iPS cells are robust and highly efficient, however, these methods involve permanent genetic modifications due to viral integrations leading to malignant transformation. Therefore, a protein-based approach to deliver biologically active recombinant proteins in somatic cells to generate iPS cells is safe and will improve the prospects of these cells from bench-to-bedside. This review provides an overview of protein-based somatic cell reprogramming to generate transgene-free iPS cells and gives a glimpse of the bottlenecks associated with this technology.